2015
DOI: 10.5811/westjem.2014.11.22495
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Rate of Testicular Salvage in Acute Testicular Torsion at a Tertiary Pediatric Center

Abstract: IntroductionStudies have demonstrated that variables other than duration of symptoms can affect outcomes in children with acute testicular torsion. We examined demographic and logistical factors, including inter-hospital transfer, which may affect outcomes at a tertiary pediatric referral center.MethodsWe reviewed charts of all pediatric patients with acute testicular torsion during a five-year period. Data were collected regarding age, insurance type, socioeconomic status, duration of symptoms prior to presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 14 publications
3
52
2
1
Order By: Relevance
“…Testicular salvage rates are 85–97% if operated on within 6 h of the initial symptoms [19]. Although the time to consultation has not been shown to be directly related to testicular loss [20], early involvement of urology is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular salvage rates are 85–97% if operated on within 6 h of the initial symptoms [19]. Although the time to consultation has not been shown to be directly related to testicular loss [20], early involvement of urology is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Males with testicular torsion most commonly present with acute scrotal/testicular pain and swelling (the acute scrotum), which can also be the presenting symptoms for epididymitis‐orchitis, torsion of the appendix testis, and scrotal trauma . Testicular torsion is caused by the twisting of the spermatic cord along with the vasculature of the testicle and requires prompt surgical intervention to prevent testicular loss from ischemia . This occurs in approximately 1 in 1,500 to 1 in 4,000 males by the age of 25 .…”
Section: Importancementioning
confidence: 99%
“…This occurs in approximately 1 in 1,500 to 1 in 4,000 males by the age of 25 . It is important to quickly differentiate between the different testicular conditions associated with the acute scrotum to optimize the time to surgery to preserve testicular viability for those with testicular torsion . One study found that for males treated within 6 hours of the onset of symptoms there is a 90% to 100% rate of testicular salvage.…”
Section: Importancementioning
confidence: 99%
“…A similar study carried out in California also showed that inter-hospital transfer certainly delayed surgical management, but did not seem to impact on testicular salvage rates. 9 Although the protocols overseas will differ from those in the UK, the recurrent theme across these studies is that outcomes are not being affected by delays following hospital assessment. Time from symptom onset to theatre may be prolonged by many factors following presentation, but most of the delay appears to be occurring prior to arrival at a medical centre.…”
Section: Should We Be Imaging?mentioning
confidence: 99%